2022
DOI: 10.3390/ijerph192214748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Cariprazine on Memory and Cognition in Experimental Rodent Models

Abstract: The main symptoms of schizophrenia are categorized as positive, negative, and cognitive. Cognitive impairments do not generally respond to antipsychotics. Cariprazine is a novel antipsychotic conceived with the idea that high affinity for D3 receptors may elicit a favorable response in the management of cognitive deficits. We evaluated the pro-cognitive properties of 14-day long pre-treatment with cariprazine (0.25, 0.5, and 1 mg/kg b.w. intraperitoneally) in experimental rodent models with scopolamine-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…However, radioligand binding studies have shown no affinity of JJGW07 for 5-HT 6 receptors, suggesting that other biological targets are involved in its pharmacological effects. Importantly, the memory-enhancing activity is not only dependent on the modulation of 5-HT 6 receptors, as there are other antipsychotics, i.e., aripiprazole, brexpiprazole, or cariprazine, that show procognitive properties due to other mechanisms, including interactions with the 5-HT 1A and/or 5-HT 7 receptors [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, radioligand binding studies have shown no affinity of JJGW07 for 5-HT 6 receptors, suggesting that other biological targets are involved in its pharmacological effects. Importantly, the memory-enhancing activity is not only dependent on the modulation of 5-HT 6 receptors, as there are other antipsychotics, i.e., aripiprazole, brexpiprazole, or cariprazine, that show procognitive properties due to other mechanisms, including interactions with the 5-HT 1A and/or 5-HT 7 receptors [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This beneficial effect on cognition is likely attributed to cariprazine's interaction with D3 receptors and agonism at 5-HT1A receptors. The cognitiveenhancing properties of cariprazine are probably the result of integrated modulation in the hippocampus, amygdala and prefrontal cortex [37].…”
Section: Pro-cognitive Effectmentioning
confidence: 99%
“…Another study showed that D 3 R partial agonist activity of cariprazine, which produced functional antagonism, was involved in increased nucleus accumbens and hippocampal neurotransmitter effect possibly contributing to its antipsychotic effect (Huang et al , 2019). Lastly, another mouse study found that cariprazine’s beneficial effect on cognition (improved learning and memory in both short-term and long-term memory) was likely due to its affinity for D 3 R (Zlatanova et al , 2022).…”
Section: Introductionmentioning
confidence: 99%